The house at Riverton : a novel - Morton, Kate, 1976- (New York : Washington Square Press, 2006)
Grace Bradley went to work at Riverton House as a servant when she was just a girl, before the First World War. For years her life was inextricably tied up with the Hartford family, most particularly the two daughters, Hannah and Emmeline. In the summer of 1924, at a glittering society party held at the house, a young poet shot himself. The only witnesses were Hannah and Emmeline and only they--and Grace--know the truth. In 1999, when Grace is ninety-eight years old and living out her last days in a nursing home, she is visited by a young director who is making a film about the events of that summer. She takes Grace back to Riverton House and reawakens her memories--From publisher description.
"Originally published in Australia in 2006 as The Shifting Fog by Allen & Unwin"--T.p. verso.
Keywords: Women household employees -- Fiction; Reminiscing in old age -- Fiction; Upper class families -- Fiction; Poets -- Crimes against -- Fiction; Great Britain -- Social life and customs -- 1918-1945 -- Fiction; England -- Fiction; Mystery fiction